2020
DOI: 10.21203/rs.3.rs-42011/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Schistosomiasis, Upper Gastrointestinal Bleeding, and Health Related Quality of Life Measurements in Rural Africa

Abstract: Introduction Health related quality of life (HRQOL) measurements, which include disability weights, are important endpoints of health care delivery. These measurements are scarce for patients with upper gastrointestinal bleeding (UGIB) in rural sub-Saharan Africa (SSA) where schistosomiasis is endemic. Methods and materials In 2014, we studied HRQOL measurements among patients with UGIB in SSA where schistosomiasis is endemic. Participants included adult inpatients and outpatients with a history of UGIB at a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…However, HRQoL data associated with S. mansoni infection are lacking worldwide and particularly within the sub-Saharan Africa context, despite 85% of schistosomiasis cases occurring in this region [9]. The effect of severe and chronic S. mansoni infection has been associated with increased morbidity and reduced HRQoL [16,17]. However, short-term effects of mild infections on HRQoL have yielded contradictory results: some studies showed negative associations among adults and children, with higher impact on emotional rather than physical dimensions [18][19][20], but others reported no associations [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…However, HRQoL data associated with S. mansoni infection are lacking worldwide and particularly within the sub-Saharan Africa context, despite 85% of schistosomiasis cases occurring in this region [9]. The effect of severe and chronic S. mansoni infection has been associated with increased morbidity and reduced HRQoL [16,17]. However, short-term effects of mild infections on HRQoL have yielded contradictory results: some studies showed negative associations among adults and children, with higher impact on emotional rather than physical dimensions [18][19][20], but others reported no associations [21][22][23].…”
Section: Introductionmentioning
confidence: 99%